(3JMaI GdeSJQTOjf aj HjGf ePGgH aQb GdeSdejfs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; hUdi Gddg Ydi SjOfG eMeO Bdg hUMHg hSde GdMeO ddg GdPj GQGfG GdMb hGQRbfG GJHGYg hHYO gPg QSGdI eNJUQI aj HjGf WQa ef ebGdGJ Cgd GdSfI GdPjf cGfhG Ydi eG cGf Ydjg QShd Gddg Udi Gddg Ydjg hSdes
(3BNQgG (B:s
(3hbGdhG ef GOYi GdNdGaI ef ChdGO Ydj jLH Ydi Cgd GdYGde fUQJg gPg HYV ebGdGJ GdaQb GdESdGejI hGYJbGOGJge , hcdge Ydi ZjQ GdMb EdG Cgd GdSfI hGdLeGYI aEfge Ydi GdMb hGdMb eYge MjK eG cGfhG fUQge Gddg JYGdi hNPd ef NGdage aj ePgHges
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3YHO Gddg YHOgs
Keywords: (3GdJhMjO hGdedd hGdfMds